4x -3x +1 = 2
1x = 2 -1
x = 1
Check
4x -(3x-1) = 2
4 -(2) = 2
2 = 2 YES
2007-10-05 11:43:36
·
answer #1
·
answered by David F 5
·
0⤊
0⤋
x=1
2007-10-05 11:44:59
·
answer #2
·
answered by 3.14 2
·
0⤊
0⤋
4x-(3x-1)=2 disribute
4x-3x+1=2
x+1=2
-1 -1
x=1
2007-10-05 11:50:55
·
answer #3
·
answered by Dr. dope 4
·
0⤊
0⤋
4x-(3x-1)=2
use the distributive property 4x-3x+1=2
subtract 1 from the equation to get x by itself 4x-3x=1
1x=1 x=1
2007-10-05 12:09:32
·
answer #4
·
answered by Anonymous
·
0⤊
0⤋
4x - (3x - 1) = 2
1x + 1 = 2
x = 2 - 1
x= 1
2007-10-05 11:45:49
·
answer #5
·
answered by Ra Ra Ha Ha 2
·
0⤊
0⤋
x + 1 = 2
x = 1
2007-10-06 02:52:09
·
answer #6
·
answered by Como 7
·
0⤊
0⤋
i got x=1
2007-10-05 11:46:55
·
answer #7
·
answered by ►bored 2
·
0⤊
0⤋
not possible
2007-10-05 11:47:57
·
answer #8
·
answered by monkey 1
·
0⤊
0⤋